History of interdental brushes: origins, developments, perspectives - Staehle, Hans Jörg; Sekundo, Caroline (Oral health & preventive dentistry, 2025)
Purpose: To trace the history of interdental brushes (IDBs) from their origins to the present, highlighting their development and future prospects compared to other interdental hygiene aids. - Methods and Materials: A literature search using digital databases, manual reviews and on-site research in museums were carried out. - Results: Although extensive literature exists on toothbrushes, flosses and toothpicks, there has been no comprehensive study of IDBs. Twisted brushes for oral hygiene were mentioned as ear-ly as the late 19th century. The exact origins of their use in interdental spaces remain unclear, but evidence narrows it to the early 20th century. IDBs have been in documented use since at least 1960, with publications emerging in the 1970s. Historically, evaluations of IDBs have been mixed, balancing high expectations with scepticism regarding efficacy and safety. By the early 21st century, IDBs were often considered superior for interdental cleaning. Advances included modifications in brush head designs, handle types, and the establishment of standards like ISO 16409, though these did not always facilitate proper selection and use. - Conclusion: Recent literature still highlights limited evidence-based statements on IDB efficacy, with some questioning their superiority over other aids like dental floss. Consumer-friendly alternatives, such as rubber picks, are sometimes rated higher, however, without allowing for a final assessment. For IDBs to meet the standards of Frugal Dentistry, they must improve oral health, be widely demanded, and cost-effective. Future research should provide more precise indications for IDBs and scientifically sound recommendations for various sizes and designs, ensuring they are easy to use and effective for different interdental spaces.
Gesehen am 08.04.2025